The pediatric indications for tonsillectomy and adenotonsillectomy: Race/ethnicity, age, and gender. Issue 2 (6th February 2023) - Han, Chihun Jim; Bergman, Maxwell; Harley, Randall J.; Harley, Earl H.
Abstract: Objective: To evaluate how pediatric indications for tonsillectomy or adenotonsillectomy relate to gender, race/ethnicity, and age. Methods: Included consecutive pediatric patients who underwent tonsillectomy or adenotonsillectomy from a single tertiary academic institution between 2012 and 2019. Logistic regression analysis was used to measure association between the indication for tonsillectomy and the demographic variables gender, race/ethnicity, and age. Results: Of the 1106 children included in this study, 53% were male and 47% were female. Half of the children were White, 40% were African American, 6% were Hispanic and 4% were other. The most common indication for surgery was upper airway obstruction alone (66%), followed by obstruction and infection (22%), and recurrent infections (12%). We found that male gender (OR 1.59, 95% CI 1.24–2.04), African American race (OR 2.76, 95% CI 2.08–3.65), and younger age were associated with greater odds of presenting with upper airway obstruction as the indication for tonsillectomy. Conversely, male gender (OR 0.63, 95% CI 0.44–0.92), African American race (OR 0.4, 95% CI 0.26–0.61), and younger age were associated with lower odds of presenting with recurrent infection as the indication for tonsillectomy. Conclusions: Male gender, African American race, and young age are risk factors for tonsillar surgery due to airway obstruction. Female gender, White race, and older age are risk factors for tonsillar surgery due to recurrent throat infections. Level of Evidence: 3 Abstract :